The Musical Self-Concept of Chinese Music Students - Petersen, Suse; Camp, Marc-Antoine (Frontiers in Psychology, 2016)
The relationship between self-concept and societal settings has been widely investigated in several Western and Asian countries, with respect to the academic self-concept in an educational environment. Although the musical self-concept is highly relevant to musical development and performance, there is a lack of research exploring how the musical self-concept evolves in different cultural settings and societies. In particular, there have been no enquiries yet in the Chinese music education environment. This study’s goal was the characterization of musical self-concept types among music students at a University in Beijing, China. The Musical Self-Concept Inquiry (MUSCI)—including ability, emotional, physical, cognitive, and social facets—was used to assess the students’ musical self-concepts (N=97). The data analysis led to three significantly distinct clusters and corresponding musical self-concept types. The types were especially distinct, in the students’ perception of their musical ambitions and abilities; their movement, rhythm and dancing affinity; and the spiritual and social aspects of music. The professional aims and perspectives, and the aspects of the students’ sociodemographic background also differed between the clusters. This study is one of the first research endeavors addressing musical self-concepts in China. The empirical identification of the self-concept types offers a basis for future research on the connections between education, the development of musical achievement, and the musical self-concept in societal settings with differing understandings of the self.